Peningkatan Hasil Belajar IPS melalui Model Pembelajaran Inkuiri Sosial pada Siswa Kelas 4 Mi Muhammadiyah Rempoa - Rosfiani, Okta; Pratama, Ruchlan Putra; Zihni, Kayla Yusrina; Ikhwan, Rafi; Nisa, Nur Azka Aulia (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This research aims to improve the Social Studies learning outcomes of 4th-grade students through the application of the social inquiry learning model at MI Muhammadiyah 01 Rempoa. The background of this research stems from the low motivation and engagement of students due to the traditional lecture method, which is less interactive. The focus of the problem lies in how the social inquiry model can address these challenges and improve student learning outcomes. This research uses the Classroom Action Research (CAR) method with cycle stages that include planning, action, observation, and reflection. Each cycle aims to improve learning strategies and measure their effectiveness through quantitative and qualitative data. The research results show a significant improvement, where 85% of students achieved scores above the Minimum Completeness Criteria (KKM) in the third cycle. The main conclusion of this research is that the social inquiry learning model has proven effective in creating active and meaningful learning, as well as enhancing students' critical thinking skills, cooperation, and understanding of the material. These findings affirm that the social inquiry approach can be an innovative solution to enhance the quality of social studies education in elementary schools.